Advance in Targeted Immunotherapy for Graft-Versus-Host Disease - Zhang, Lingling; Yu, Jianhua; Wei, Wei (Frontiers in Immunology, 2018)
Graft-versus-host disease (GVHD) is a serious and deadly complication of patients, who undergo hematopoietic stem cell transplantation (HSCT). Despite prophylactic treatment with immunosuppressive agents, 20% to 80% of recipients develop acute GVHD after HSCT. And the incidence rates of chronic GVHD range from 6 to 80%. Standard therapeutic strategies are still lacking, although considerable advances have been gained in knowing of the predisposing factors, pathology and diagnosis of GVHD. Targeting immune cells, such as Tregs, as well as tolerogenic dendritic cells (TDCs) or mesenchymal stromal cells (MSCs) display considerable benefit in the relief of GVHD through the deletion of alloactivated T cells. Monoclonal antibodies targeting cytokines or signaling molecules have been demonstrated to be beneficial for the prevention of GVHD. However, these remain to be verified in clinical therapy. It is also important and necessary to consider adopting individualized treatment based on GVHD subtypes, pathological mechanisms involved and stages. In the future, it is hoped that the identification of novel therapeutic targets and systematic research strategies may yield novel safe and effective approaches in clinic to improve outcomes of GVHD further. In this article, we reviewed the current advances in targeted immunotherapy for the prevention of GVHD.